Complete immunization against Trypanosoma cruzi verified in individual mice by complement-mediated lysis - Laura E Gómez; Julio R Nasser; Miguel A Basombrío (Memorias do Instituto Oswaldo Cruz, 1996)
Experimental systems to assay immunity against Trypanosoma cruzi usually demonstrate partial resistance without excluding the establishment of sub-patent infections in protected animals. To test whether Swiss mice immunized with attenuated parasites might develop complete resistance against virulent T. cruzi, experiments were performed involving challenge with low numbers of parasites, enhancement of local inflammation and the combination of natural and acquired resistance. Absence of infection was established after repeated negative parasitological tests (including xenodiagnosis and hemoculture), and lack of lytic antibody was tested by complement mediated lysis. Immunization with 10(7) attenuated epimastigotes conferred protection against the development of high levels of parasitemia after challenge with Tulahuen strain, but was unable to reduce the number of infected animals. However, when a strong, delayed-type hypersensitivity reaction was triggered at the site of infection by injecting a mixture of virulent and attenuated T. cruzi, a significant proportion of immunized animals remained totally free of virulent infection. The same result was obtained when the immunization experiment was performed in four month old Swiss mice, displaying a relatively high natural resistance and challenged with wild, vector-borne parasites. These experiments demonstrate that complete resistance against T. cruzi can be obtained in a significant proportion of animals, under conditions which replicate natural, vector delivered infection by the parasite.